Model for Determining the Optimum Marketing Strategy for Schneider Electric Products Using Game Theory Approach (Case Study: Authorized Distributor Schneider Electric) - Ridho Habibi, Anggi; Sembiring, Meilita Tryana; Anizar, Anizar (Jurnal Sistem Teknik Industri, 2025)
Market competition, sales area, and similar business process between authorized distributors of Schneider Electric Medan namely KAK and PJ have an impact on the problems experienced by consumers, resulting in sales decrease and unachieved targets by distributors. Optimal marketing strategy modeling for each distributor is needed to restore consumer confidence and also increase sales. Game theory is used to analyze the most optimum applications by finding the best mathematical model for each distributor, where each player is expected to find the most optimum indicator in maximizing profits or minimizing losses. The novelty in this study is related to the application of strategy implementation (sub-variables) which will be actions that can be taken in implementing selected strategies (main variables) for each distributor. The results of the study show that the optimum marketing strategy of the main variable for KAK is the payment strategy, and for PJ is the aftersales strategy, with the saddle point value of the game is 17.73. The applications of the optimum marketing strategy for KAK payment strategy are COD, Net OEMD, and CIA, while for PJ aftersales strategy are Warranty, Technician, and Service Center, with the saddle point value of the game is 28.18.